Anti-Müllerian hormone (Amh/amh) plays dual roles in maintaining gonadal homeostasis and gametogenesis in zebrafish. (1st November 2020) - Zhang, Zhiwei; Zhu, Bo; Chen, Weiting; Ge, Wei
Abstract: Anti-Müllerian hormone (AMH/Amh) plays a role in gonadal differentiation and function across vertebrates. In zebrafish we demonstrated that Amh deficiency caused severe gonadal dysgenesis and dysfunction. The mutant gonads showed extreme hypertrophy with accumulation of early germ cells in both sexes, namely spermatogonia in the testis and primary growth oocytes in the ovary. In amh mutant females, the folliculogenesis was normal in young fish but receded progressively in adults, which was accompanied by progressive decrease in follicle-stimulating hormone ( fshb ) expression. Interestingly the expression of fshb increased in the pituitary of juvenile amh mutant males but decreased in adults. The upregulation of fshb in mutant male juveniles was likely one of the mechanisms for triggering gonadal hypergrowth, whereas the downregulation of fshb in adults might involve a negative feedback by gonadal inhibin. Further analysis using mutants of fshb and growth differentiation factor 9 ( gdf9 ) provided evidence for a role of FSH in triggering ovarian hypertrophy in young female amh mutant as well. In summary, the present study provided comprehensive genetic evidence for dual roles of Amh in controlling zebrafish gonadal homeostasis and gametogenesis in both sexes. Amh suppresses proliferation or accumulation of early germ cells (spermatogonia in testis and primary growth oocytes in ovary) while promoting their exit to advanced stages, and its action may involve both endocrine and paracrine pathways.